Age-Associated Changes of Nasal Bacterial Microbiome in Patients With Chronic Rhinosinusitis - Chen, Fang; Gao, Wenxiang; Yu, Chaosheng; Li, Junzheng; Yu, Feng; Xia, Meng; Liang, Jiajian; Shi, Jianbo; Lai, Yinyan (Frontiers in Cellular and Infection Microbiology, 2022)
Age-related changes in nasal bacterial microbiota of patients with chronic rhinosinusitis (CRS) remains unclear. In this study, we aimed to identify distinct characteristics of nasal bacterial microbiota between aged and younger patients with CRS through 16S rDNA gene sequencing. Patients with CRS undergoing endoscopic sinus surgery were recruited and separated into aged (≥60 years, median age = 66 years, N = 17) and younger (<60 years, median age = 35.5 years, N = 14) patients. Diversity, bacterial composition and metabolic activities of nasal microbiota between aged and younger patients were compared. Results have shown that levels of OTUs (p = 0.0173) and microbiota diversity (all p < 0.05) decreased significantly in aged patients. The abundance of phylum Actinobacteria, and genus Corynebacterium were significantly higher in aged patients, while the abundance of phylum Bacteroidetes, Fusobacteria, and genus Fusobacterium, Peptoniphilus were significantly higher in younger patients. In addition, predicted functional profiles have revealed that 41 KEGG pathways involving in 12 metabolic pathways, 4 genetic information processing, 3 environmental information processing, 4 cellular processes, 8 organismal systems, 6 human diseases, and 4 unclassified pathways were identified. Among which, the vast majority of metabolic activities are involved in replication and repair, membrane transport, translation, and the metabolism of amino acid, carbohydrate, energy, cofactors and vitamins, and nucleotide. On the level of the thirdly bacterial metabolic pathways, purine metabolism, glycine, serine and threonine metabolism, valine, leucine and isoleucine biosynthesis, glycolysis/gluconeogenesis and phenylalanine, tyrosine and tryptophan biosynthesis are significantly up-regulated while carbon fixation pathways in prokaryotesand methane metabolism are significantly down-regulated in aged patients. Overall, our analysis revealed that age-related physiological and pathological changes on the nasal mucosal surface may alter the host immune response and be highly associated with the nasal bacterial microbiota of patients with CRS. However, future studies are needed to elucidate the causal relationship.